Financial liberalization and Fdi in Malaysia - Ho, Chia Lee (Universiti Malaysia Sarawak, (UNIMAS), 2010)
([his study aims to examine whether economic growth, interest rate and financial development, lead to FDI growth or vice versa in the small open economy of Malaysia. Covering the period from 1999:Ql to 2007:Q4, we re-examine the robustness of the relationship between FDI and economic growth, interest rate and financial development by using three types of methods: (1) the Augmented Dickey-Fuller (ADF) unit root test, (2) the Johansen and Juselius co-integration test, and (3) the Granger causality tes;) Results of these three methods indicated that economic growth, interest rate and financial development in Malaysia do affect the flow of FDI towards Malaysia. The findings also provide some support for the necessity of a well-functioning financial system in order to achieve high economic growth. Our findings also indicate that the interest rate played a role in enhancing financial development. This study further showed that a Granger-caused link exists between economic growth, interest rate, financial development and FDI - these are significantly interrelated. Given the strong evidence from the empirical results, we advocate that increased liberalization in the financial sector could help to attract more foreign investment towards Malaysia, the result of which is stronger economic growth.